2022
DOI: 10.1021/acsnano.1c11442
|View full text |Cite
|
Sign up to set email alerts
|

ZnSe Nanorods–CsSnCl3 Perovskite Heterojunction Composite for Photocatalytic CO2 Reduction

Abstract: Utilizing sunlight to convert CO 2 into chemical fuels could simultaneously address the greenhouse effect and fossil fuel crisis. ZnSe nanocrystals are promising candidates for photocatalysis because of their low toxicity and excellent photoelectric properties. However, pristine ZnSe generally has low catalytic activities due to serious charge recombination and the lack of efficient catalytic sites for CO 2 reduction. Herein, a ZnSe nanorods−CsSnCl 3 perovskite (ZnSe−CsSnCl 3 ) type II heterojunction composite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
147
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 264 publications
(147 citation statements)
references
References 57 publications
0
147
0
Order By: Relevance
“…Furthermore, severe electron/hole recombination and slow surface reaction kinetics limit the photocatalytic performance. [5,6] Therefore, the focus of the current research is to design materials that can reduce the activation energy required for reduction reactions, increase the amount of photogenerated electrons, and accelerate the separation of electrons and holes to improve CO 2 reduction efficiency and product selectivity. [7,8] Among the developed photocatalysts, transition metal hydroxides, as noble-metal-free cocatalysts, are attractive because they are naturally abundant, cost effective, and have high CO 2 adsorption capacity.…”
mentioning
confidence: 99%
“…Furthermore, severe electron/hole recombination and slow surface reaction kinetics limit the photocatalytic performance. [5,6] Therefore, the focus of the current research is to design materials that can reduce the activation energy required for reduction reactions, increase the amount of photogenerated electrons, and accelerate the separation of electrons and holes to improve CO 2 reduction efficiency and product selectivity. [7,8] Among the developed photocatalysts, transition metal hydroxides, as noble-metal-free cocatalysts, are attractive because they are naturally abundant, cost effective, and have high CO 2 adsorption capacity.…”
mentioning
confidence: 99%
“…3b). 57 Meanwhile, the arc radius in the electrochemical impedance spectroscopy (EIS) Nyquist plots (Fig. 3c) changes with the ligand vacancy and defect nature in the MOFs, as UiO-66-NH 2 -ML-100 has the smallest semicircular radius, manifesting the lowest charge transfer resistance in defect MOFs.…”
Section: Resultsmentioning
confidence: 99%
“…The reduced exciton lifetime confirmed accelerated photoexcitation dissociation in CdS, suggesting that electrons transported from CdS to CuS via a nonradiative quenching manner. 61,62 Additionally, the transient photocurrent response (Fig. S11 †) indicated that CdS-CuS-2 exhibited a higher photocurrent over CdS/CuS-2 and CuS, which suggested a superior carrier separation ability and more efficient charge transfer in CdS-CuS-2.…”
Section: Optical and Electrochemical Analysesmentioning
confidence: 97%